Leaf color chart for managing nitrogen fertilizer in lowland rice in Bangladesh - Alam, M. Murshedul; Ladha, J.K.; Khan, S. Rahman; Foyjunnessa; Harun-ur-Rashid; Khan, A.H.; Buresh, R.J. (Wiley, 2005)
Nitrogen (N) fertilizer, while essential for high yield and profit in rice (Oryza sativa L.) farming, is often managed inefficiently by Asian rice farmers. We evaluated the leaf color chart (LCC) as a simple tool for improving the time and rate of N fertilizer use in farmers’ fields with no limitation in water supply in southwestern Bangladesh. Use of the LCC for N management consistently increased grain yield and profit as compared with the farmers’ fertilizer practice across the three wet (Aman) and three dry (Boro) seasons, which each involved 1 to 5 villages and a total of 8 to 36 farmers. Use of the LCC for N management without any other change in the farmers’ fertilizer or crop management increased average grain yield by 0.1 to 0.7 Mg ha−1 across villages and seasons. This corresponded to an average added net return of US$ 41 to 65 ha−1 season−1, which arose largely because of increased yield. Grain yields were increased by an additional ≥0.3 Mg ha−1 at about half the combinations of villages and seasons when the LCC was combined with recommended P, K, S, and Zn fertilization. Grain yields were further increased by another ≥0.4 Mg ha−1 at about half the combinations of villages and seasons when the LCC and recommended P, K, S, and Zn fertilization were combined with improved crop management, involving the recommended manual weed control and plant spacing. Use of the LCC with rice is ready for wide‐scale promotion in Bangladesh.